(untitled) (Research, Society and Development, 2022)
Purpose: To compare the stability and bone loss of implants installed in the maxillary sinus after sinus lift using Bio-ossä Small and Large, before functional loading (T1) and after it (T2). Methods: Ten patients received bone graft in the maxillary sinus in two different granulations: Bio-ossä Small and Large, with one granulation per sinus. After 8 months, the implants were installed. Prosthesis manufacturing and installation occurred after a six-month. Out of 10 patients, six (13 implants) were selected, with an average age of 53.4 years. The stability was measured with a resonance frequency and all implants installed showed high values in both groups. Results: The comparison between times showed a statistical difference with the Bio-ossä Large particles, in which T1 (64.21±7.41) was lower than T2 (69.96±4.95; P=0.003). However, the comparison between the different particle dimensions in the same period didn’t show a statistical difference. Regarding marginal bone loss, there wasn’t statistical difference between the particle dimensions. There wasn’t correlation between stability and marginal bone loss and between the different biomaterial particle dimensions. Conclusion: The implants installed in grafted maxillary sinus with both Bio-Ossä particle dimensions showed similar behavior, allowing implant stability and functional loading.